(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Converting waste into biogas has the benefits of reducing emission to the atmosphere and adding energy to the society for improving livelihood of the people. An extensive amount of food waste is generated regularly from residential area, student hostels, restaurants, markets. Thus food waste can be a fruitful alternative for biogas production. Therefore, an experimental research work was commenced at the GEKH (Green Energy Knowledge Hub) laboratory of the department of Farm Power and Machinery, Bangladesh Agricultural University to analyze the potentiality of biogas production of different food wastes. Four ladies halls were selected for the study. An approximate amount of total food waste of these halls was estimated through survey and visual inspection. Furthermore, food wastes were collected from these halls for conducting batch experiment for understanding gas production potential from the wastes. Food wastes such as various vegetable wastes like potato, cauliflower, cabbage, bean; chicken slaughter and fish waste were classified; wastes from the plates were selected for this study. The whole experiment was conducted in an incubator where all the substrates were mixed with a seeding inoculum (same volatile solid ratio) for 54 days retention time with three replications at 35˚C temperature. Total waste production from the four female student halls was 860 kg/day among which vegetable wastes was 40%, slaughter and fish wastes was 20% and wastes from peoples plate was 40%. It was found that slaughter and fish waste mixture was more potential substrate in biogas production than other selected substrates respectively. The cumulative biogas production of slaughter and fish waste mixture and cumulative bio-methane potentiality of slaughter and fish waste mixture were found 256.13 ml/g VS and 190.08 ml/g VS, respectively. From the total wastes, about 11.68 m³/day methane can be produced for mixed type waste by which 44.16% natural gas consumption of four student halls can be substituted. J Bangladesh Agril Univ 18(1): 138–144, 2020 https://doi.org/10.5455/JBAU.75078